Hydrogen peroxide and cell signaling part C - Cadenas, Enrique; Packer, Lester (Amsterdam, Netherlands Elsevier/ Academic Press, 2013)
This new volume of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This is the third of three volumes on hydrogen peroxide and cell signaling, and includes chapters on such topics as the biological chemistry of hydrogen peroxide, reactive oxygen species in the activation of MAP kinases, and investigating the role of reactive oxygen species in regulating autophagy. Continues the legacy of this premier serial with quality chapters authored by leaders in the field.
Front Cover; Hydrogen Peroxide and Cell Signaling, Part C; Copyright; Contents; Contributors; Preface; Methods in Enzymology; Section I: H2O2 Regulation of Cell Signaling; Chapter One: The Biological Chemistry of Hydrogen Peroxide; 1. Introduction; 2. Chemical Properties; 2.1. Two-electron oxidations; 2.1.1. Thiols; 2.1.2. Keto acids; 2.1.3. Carbon dioxide; 2.1.4. Explaining the high reactivity of thiol peroxidases; 2.2. Reactions with transition metals and one-electron oxidations; 2.2.1. Transition metals and Fenton chemistry.
Includes bibliographical references and index.
Keywords: Cell interaction; Hydrogen peroxide; Electronic books